The linkage between phytoplankton productivity and photosynthetic electron transport in the summer from the Changjiang River to the East China Sea - Fei, Shuyi; Gao, Yonghui; Li, Ji; Cao, Lingzhi (Frontiers in Marine Science, 2024)
Variable fluorescence measurements provide automatic and rapid estimates of electron-based photosynthesis. However, electron transport rates (ETR) to phytoplankton production vary greatly due to biological physiology and environmental stress along the Changjiang River to the adjacent seawater, where the turbid riverside, nutrient-rich river plume, and seawater are divided by the sediment front and plume front. We assessed the light responses of ETR, 18O-labeled gross primary production (GPP), and O2-based net community production (NCP) during the bloom season at the Changjiang River Estuary. The distribution of phytoplankton and potential photosynthesis efficiency were positively correlated, exhibiting offshore decreasing trends and peaking around the upwelling areas. The conversion factors of ΦGPP (mol e- per mol O2 production) ranged from 0.8 to 31.8, and ΦNCP ranged from 0.9 to 36.9, respectively. Φe: O increased from the nutrient-rich Changjiang diluted water (CDW) to the nutrient-poor seawater. Although ΦGPP and ΦNCP were linearly related to non-photochemical quenching (R2 > 0.5) in the CDW, this relationship was decoupled in offshore seawater due to P-limitation, light stress, and shifts in the phytoplankton community. A better relationship between ΦGPP and ΦNCP was quantified using multiple linear analyses with the light attenuation coefficient (Kd), euphotic depth (Zeu), salinity, nutrients, and temperature (p< 0.001). This improvement in accuracy represents a major step forward for widespread and accurate fluorometry-based GPP and NCP applications at high temporal and spatial resolutions in the future.